Optimal pre-exam self-study time under states of stress - ÇİLİNGİRTÜRK, AHMET METE (My University, 2023)
Extracurricular teaching activities such as self-study and project assignments are educational policies. The aim of these policies is to raise individuals equipped with the knowledge needed for the economy as well as to increase student performance. The amount of knowledge is measured by grades in exams. However, most students study before exams to partially bridge this gap. Stress mediates the relation of study effort to academic performance. Thus, students should attempt to study self for the optimum time period when preparing for exams under stress. This research estimates the optimal self-study time before examination for social science students for a mathematical course. The situation was approached as a decision-making problem under risk. A period of 30 hours is calculated as efficient for the study time before the exams, such as when calculating ECTS’s.